Certificate of need laws and health care use during the COVID-19 pandemic - Agnitra Roy Choudhury; Sriparna Ghosh; Alicia Plemmons (Journal of Risk and Financial Management, 2022)
This paper investigates the impact of state-level Certificate-of-Need (CON) laws on COVID and non-COVID deaths in the United States during the SARS-CoV-2 pandemic. CON laws limit the expansion and acquisition of new medical services, such as new hospital beds. The coronavirus pandemic created a surge in demand for medical services, which might be exacerbated in some states that have CON laws. Our investigation focuses on mortality due to COVID and non-COVID reasons and understanding how these laws affect access to healthcare for illnesses that might require similar medical equipment to COVID patients. We find that states with high healthcare use due to COVID that reformed their CON laws during the pandemic had a reduction in mortality resulting from COVID-19, septicemia, diabetes, chronic lower respiratory disease, influenza or pneumonia, and Alzheimer's Disease, relative to non-reforming CON states.
Keywords: 330; Certificate of Need; healthcare; regulation; COVID-19; mortality